Porter's value chain and the REA analysis as an accounting information system - Bischoff, Anna Lena (Norderstedt: Grin Verlag, 2011)
The content covers: 1. Introduction. 2. Value System Model. 3. Business Processes. 4. The REA Analysis.
rpm 06/12/2017
Loans
Keywords: Management accounting; Accounting information systems; Accounting